Growth and Fabrication of High‐Quality Single Nanowire Devices with Radial p‐i‐n Junctions. Issue 3 (17th December 2018) - Zhang, Yunyan; Sanchez, Ana M.; Aagesen, Martin; Huo, Suguo; Fonseka, H. Aruni; Gott, James A.; Kim, Dongyoung; Yu, Xuezhe; Chen, Xingyou; Xu, Jia; Li, Tianyi; Zeng, Haotian; et al.
Abstract: Nanowires (NWs) with radial p‐i‐n junction have advantages, such as large junction area and small influence from the surface states, which can lead to highly efficient material use and good device quantum efficiency. However, it is difficult to make high‐quality core–shell NW devices, especially single NW devices. Here, the key factors during the growth and fabrication process that influence the quality of single core–shell p‐i‐n NW devices are studied using GaAs(P) NW photovoltaics as an example. By p‐doping and annealing, good ohmic contact is achieved on NWs with a diameter as small as 50–60 nm. Single NW photovoltaics are subsequently developed and a record fill factor of 80.5% is shown. These results bring valuable information for making single NW devices, which can further benefit the development of high‐density integration circuits. Abstract : Single nanowire (NW) devices with radial p‐i‐n junctions are difficult to make. Using GaAs(P) NW photovoltaics as an example, the key affecting factors during nanowire growth and device fabrication are studied in detail and a record fill factor of 80.5% is achieved.